2011
DOI: 10.3354/cr01060
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of agricultural drought using the CERES-Wheat model: a case study of Henan Plain, China

Abstract: Droughts caused by a lack of precipitation are one of the major factors limiting agricultural crop production. It is thus important to assess the risk of such droughts in order to reduce their effect on agriculture. In the present study, the drought risk for crop production was assessed through an integrated approach that analyzed the relationship between crop yield and drought on the Henan Plain, China. We used the calibrated CERES-Wheat model to simulate 2 levels of wheat yield, the yield potential and the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Ahsan and Warner [16] developed socioeconomic vulnerability index and opined that in the absence of direct methods of validation of such composite index, selection of indicators and assignment of weights are the strongest determinants of the composite index. Zhao et al [45] and Boubcar [46] revealed the agreement between drought occurrence and crop yield changes. Taking clue from these studies, we have followed an indirect approach for validation of the present vulnerability map by showing an empirical evidence on crop yield variability of major crops in different vulnerability classes.…”
Section: Categorization Of Mandals Based On Ei Is Shown Inmentioning
confidence: 85%
“…Ahsan and Warner [16] developed socioeconomic vulnerability index and opined that in the absence of direct methods of validation of such composite index, selection of indicators and assignment of weights are the strongest determinants of the composite index. Zhao et al [45] and Boubcar [46] revealed the agreement between drought occurrence and crop yield changes. Taking clue from these studies, we have followed an indirect approach for validation of the present vulnerability map by showing an empirical evidence on crop yield variability of major crops in different vulnerability classes.…”
Section: Categorization Of Mandals Based On Ei Is Shown Inmentioning
confidence: 85%
“…CERES-Wheat has been widely applied at the regional scale (e.g. Bannayan et al, 2003;Zhao et al, 2011) and preferred for the simulation of winter wheat growth at field scale in semi-arid conditions in Spain after a detailed comparison (Castañeda-Vera et al, 2015).…”
Section: Attainable Rainfed Yieldsmentioning
confidence: 99%
“…Air temperatures in this region are estimated to have increased over the past 50 years, with a rate of 0.38 C per decade. These large increases in temperature are thought to have considerable impacts on the agricultural climatic resources (Walker and Schulze, 2008;Zhao et al, 2010;Chen et al, 2011;Yuan et al, 2012;Guo et al, 2013), maize growth and harvest (Tao et al, 2008;Chen et al, 2011), crop yield (Wolf and Van Diepen, 1995;Jones and Thornton, 2003;Tao and Zhang, 2010;Zhao et al, 2011), and northern planting limits (Liu et al, 2013;Zhao and Guo, 2013). For example, Guo et al (2013) predicted the effects of climate change on the agricultural climatic resource utilization from 1951 to 2100, using the high-resolution RegCM3 (0.25 Â 0.25 ) daily data.…”
Section: Introductionmentioning
confidence: 97%